2019
DOI: 10.3390/nano9040584
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Reduction of Graphene Oxide Mitigates Its In Vivo Genotoxicity Toward Xenopus laevis Tadpoles

Abstract: The worldwide increase of graphene family materials raises the question of the potential consequences resulting from their release in the environment and future consequences on ecosystem health, especially in the aquatic environment in which they are likely to accumulate. Thus, there is a need to evaluate the biological and ecological risk but also to find innovative solutions leading to the production of safer materials. This work focuses on the evaluation of functional group-safety relationships regarding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 98 publications
1
29
0
Order By: Relevance
“…Moreover, hydroxynaphthalene derivatives such as rGO were demonstrated as estrogen receptor modulators [59]. Our in silico mutagenicity screening studies of these nanomaterials (Table S2) using Sarah Nexus (Sarah Nexus: 3.0.0, Sarah Model: 2.0) also suggested that graphene, GO and rGO may be mutagenic, supported by in vitro and in vivo studies using graphene quantum dots [60], GO [61] and rGO [62]. Therefore, the specific method to use drug delivery devices based on these composites needs to be considered.…”
Section: Resultsmentioning
confidence: 58%
“…Moreover, hydroxynaphthalene derivatives such as rGO were demonstrated as estrogen receptor modulators [59]. Our in silico mutagenicity screening studies of these nanomaterials (Table S2) using Sarah Nexus (Sarah Nexus: 3.0.0, Sarah Model: 2.0) also suggested that graphene, GO and rGO may be mutagenic, supported by in vitro and in vivo studies using graphene quantum dots [60], GO [61] and rGO [62]. Therefore, the specific method to use drug delivery devices based on these composites needs to be considered.…”
Section: Resultsmentioning
confidence: 58%
“…As already reported in the literature, oxidative stress was suggested as one mechanism involved in the genotoxic responses observed [ 2 , 3 , 4 , 9 ]. Co-exposure to nanomaterials and other compounds can affect the genotoxicity [ 2 , 6 ].…”
mentioning
confidence: 73%
“…In addition to classical cell lines such as hamster and human fibroblasts [ 1 , 2 ] or human lung cells [ 3 , 4 ], new models have been also used for investigating nanomaterials genotoxicity: ToxTracker reporter cell lines [ 5 ], human amniotic cells [ 6 ] and 3D HepG2 spheroids [ 7 ]. In this issue, three papers also deal with in vivo studies: on the plant Allium cepa [ 8 ], on the tadpoles of Xenopus laevis [ 9 ] and on rats [ 10 ]. Moreover, a broad range of nanomaterials have been tested, including plastic particles [ 2 ] that recently became of increasing concern for environmental and public health.…”
mentioning
confidence: 99%
See 2 more Smart Citations